Feature of design of the distillation unit in recycled systems - S. L. Nazanskiy; A. V. Solokhin; A. V. Kiyko (Тонкие химические технологии, 2015)
On example of the А+В↔С reaction which is situated in zeotropic mixture the different variants of separation unit design are suggested. Presented separation unit includes both two simple distillation columns and one side stream column. The separation unit allows obtaining high values of reagents conversion. The reactive distillation flow sheets are suggested also. Obtained results are confirmed by numerical simulation.and the quality of the separation process.